Tennis training model to improve groundstroke skills in children - Ngatman Ngatman; Guntur Guntur; Ismail Gani; Danang Pujo Broto (Jurnal Cakrawala Pendidikan, 2023)
The purpose of this study is to develop an effective training model for practising basic tennis groundstrokes for children aged 8-12 years old based on the action method coaching framework. Adopting the research and development stages as suggested by Borg and Gall (2003), this study included such stages as conducting preliminary research, identifying the theoretical bases for the model, designing the model, developing the components of exercises, and validating the finished model. The present study employed several methods including in-depth interviews, literature studies, as well as Delphi method to seek experts’ judgement. The data were analyzed by considerations of data reduction and thematic coding before the results were presented and conclusions were drawn. Additionally, this study also incorporated some close-ended questionnaire items and analyzed them by means of descriptive statistics to further confirm the findings. The findings suggest that the groundstroke training model based on the action method developed is declared feasible and approved for future small-scale field testing.